Consistency Of Definition Of Orthogonality In A Partial Metric Induced By A Metric - Mochammad Hafiizh; Nila Puspita Dewi; Sisworo; Dahliatul Hasanah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2023)
An extension of the metric space in which the distance of the same point is not always zero is called a partial metric space. Orthogonality is the relation of two perpendicular lines at one point of intersection forming a right angle. There are several ways to define orthogonality, including Pythagorean Orthogonality, Isosceles Orthogonality, and Birkhoff-James Orthogonality. The purpose of this research is to study the consistency of the definition of orthogonality in the metric space to the partial metric space. Based on these results, it can be concluded that the partial metric space can be obtained by linear induction from a metric space. Then, in developing the definition of orthogonality to the partial metric space, it can be concluded that the qualified orthogonality is the I-orthogonality and the BJ-orthogonality, while the P-orthogonality does not qualify the consistency of the definition of orthogonality in the partial metric space. Kata Kunci: Orthogonality, Consistency, and Partial metric space